Prevalence of physical activity counseling in primary care: A systematic review and meta-analysis - Apichai Wattanapisit; Sarawut Lapmanee; Sirawee Chaovalit; Charupa Lektip; Palang Chotsiri (Tabriz University of Medical Sciences, 2023)
Background: This systematic review aimed to summarize and evaluate the prevalence of physical activity (PA) counseling in primary care. Methods: Five databases (CINAHL Complete, Embase, Medline, PsycInfo, and Web of Science) were searched. Primary epidemiological studies on PA counseling in primary care were included. The Joanna Briggs Institute critical appraisal checklist for studies reporting prevalence data was used to assess the quality of studies. The review protocol was registered with PROSPERO (CRD42021284570). Results: After duplicate removal, 4990 articles were screened, and 120 full-text articles were then assessed. Forty studies were included, with quality assessment scores ranging from 5/9 to 9/9. The pooled prevalence of PA counseling based on 35 studies (199830 participants) was 37.9% (95% CI 31.2 to 44.6). The subgroup analyses showed that the prevalence of PA counseling was 33.1% (95% CI: 22.6 to 43.7) in females (10 studies), 32.1% (95% CI: 22.6 to 41.7) in males (10 studies), 65.5% (95% CI: 5.70 to 74.1) in people with diabetes mellitus (6 studies), 41.6% (95% CI: 34.9 to 48.3) in people with hypertension (5 studies), and 56.8% (95% CI: 31.7 to 82.0) in people with overweight or obesity (5 studies). All meta-analyses showed high levels of heterogeneity (I2=93% to 100%). Conclusion: The overall prevalence of PA counseling in primary care was low. The high levels of heterogeneity suggest variability in the perspectives and practices of PA counseling in primary care. PA counseling should be standardized to ensure its optimum effectiveness in primary care.